Patient-specific design of a soft occluder for the left atrial appendage. (January 2018) - Robinson, Sanlin; Alaie, Seyedhamidreza; Sidoti, Hannah; Auge, Jordyn; Baskaran, Lohendran; Avilés-Fernández, Kenneth; Hollenberg, Samantha; Shepherd, Robert; Min, James; Dunham, Simon; Mosadegh, Bobak
Abstract 3D printing has been used to create a wide variety of anatomical models and tools for procedural planning and training. Yet, the printing of permanent, soft endocardial implants remains challenging because of the need for haemocompatibility and durability of the printed materials. Here, we describe an approach for the rapid prototyping of patient-specific cardiovascular occluders via 3D printing and static moulding of inflatable silicone/polyurethane balloons derived from volume-rendered computed tomography scans. We demonstrate the use of the approach, which provides custom-made implants made of high-quality, durable and haemocompatible elastomeric materials, in the fabrication of devices for occlusion of the left atrial appendage—a structure known to be highly variable in geometry and the primary source of stroke for patients with atrial fibrillation. We describe the design workflow, fabrication and deployment of patient-specific left atrial appendage occluders and, as a proof-of-concept, show their efficacy using 3D-printed anatomical models, in vitro flow loops and an in vivo large animal model. A patient-specific soft cardiovascular occluder made via three-dimensional printing and static moulding of an inflatable polymer balloon on the basis of data derived from computed tomography scans of a large animal is implanted in the same animal.